1994
DOI: 10.1523/jneurosci.14-05-03180.1994
|View full text |Cite
|
Sign up to set email alerts
|

Regional and developmental heterogeneity in splicing of the rat brain NMDAR1 mRNA

Abstract: Developmental and regional alternative splicing of the NMDAR1 subunit gene transcript was examined by in situ hybridization in the developing and adult rat brain. NMDAR1 mRNA, barely detectable at embryonic day 14, increased gradually during development until the third postnatal week, after which it declined slightly to adult levels, when it was detected in every examined neuronal type. Each splice form of the primary NMDAR1 gene transcript was found to follow a parallel profile of abundance in the brain, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
218
2
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(246 citation statements)
references
References 23 publications
(65 reference statements)
24
218
2
2
Order By: Relevance
“…Relatively higher uses of the C2Ј cassette in the cerebellum and of the C1 and C2 cassettes in the cerebral cortex are generally consistent with previous studies by in situ hybridization and immunoblot analyses (Laurie and Seeburg, 1994;Al-Hallaq et al, 2001). In the present study, C-terminal cassette-dependent differences of the GluR1 subunit were also appreciated in the brain in vivo.…”
Section: Terminus-dependent Self-er Export Mechanisms In Neurons Insupporting
confidence: 92%
“…Relatively higher uses of the C2Ј cassette in the cerebellum and of the C1 and C2 cassettes in the cerebral cortex are generally consistent with previous studies by in situ hybridization and immunoblot analyses (Laurie and Seeburg, 1994;Al-Hallaq et al, 2001). In the present study, C-terminal cassette-dependent differences of the GluR1 subunit were also appreciated in the brain in vivo.…”
Section: Terminus-dependent Self-er Export Mechanisms In Neurons Insupporting
confidence: 92%
“…A previous single cell PCR study has shown that NMDAR1 mRNA is present within dendrites (Miyashiro et al, 1994), which is consistent with results showing clear dendritic localization of NMDAR1 mRNA within dendrites of cultured hippocampal neurons (Benson 1997;present study). However, previous localization studies in vivo have not shown any evidence of a dendritic distribution (Moriyoshi et al, 1991;Laurie and Seeburg, 1994). This discrepancy most likely reflects very low basal levels of dendritic NMDAR1 mRNA, which become suprathreshold for overt detectability after perforant path lesion.…”
Section: Localization Of Nmdar1 Mrna Within Dendritesmentioning
confidence: 77%
“…In rat brain, ζ1-a splice forms have been found to be the most abundant form of splice variants and are expressed all throughout the brain (Laurie and Seeburg, 1994;Laurie et al, 1995). A higher expression of ζ1-a mRNA in the 26-month old animals indicated that there was a higher amount of receptor protein without the N1 insert.…”
Section: Mrna Expression Of ζ1 Splice Formsmentioning
confidence: 99%
“…Depending on whether the N1, C1 or C2 cassettes are present or absent, they make eight different splice variants. The splice variants of NR1 (ζ1) present in the receptor complex determine a number of properties of the ion channel, such as affinity to agonist and antagonists, zinc modulation and spatio-temporal expression in the brain (Dingledine et al, 1999;Laurie and Seeburg, 1994;Prybylowski and Wolfe, 2000;Zhong et al, 1995). Due to these properties, differential effects of aging on the different splice variants could lead to important changes in the physiology and pharmacology of the NMDA receptor in the aged brain.…”
Section: Introductionmentioning
confidence: 99%